(untitled) (Research, Society and Development, 2024)
Leprosy is an infectious disease with a chronic course, whose etiological agent is Mycobacterium leprae, which mainly affects the skin and peripheral nerves. The general objective was to describe the socioeconomic and cultural challenges faced by a young person with Leprosy. The research was based on a case report and a bibliographical review of an exploratory and descriptive nature, using qualitative methods and approaches. The research participant was a valuable source, contributing through the application of a guided interview, as a qualitative and previously validated collection instrument. Enabling authors to understand the processes the patient went through, in addition to providing essential information to support the scientific basis and clinical reasoning of the study. This project stood out for its multifaceted relevance, addressing the socioeconomic challenges and stigma related to leprosy. By raising awareness about the disease and its implications, the study can influence public health policies and improve health services, as well as contribute to targeted social interventions.